Persepsi Terhadap Kualitas Calon Legislatif (Caleg), Dan Kepercayaan Politik (Political trust) dengan Partisipasi Politik. - Handaningrum, Rohana; Rini, Rr. Amanda Pasca (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. This study aims to determine the relationship of perception of the quality of candidates and political trust with political participation. The population in this study were students at the University August 17, 1945 Surabaya who already have the right to vote or voting rights (age> 17 years or married). While the sample in this study was 150 students, with incidental sampling method. The results of this study were analyzed using multiple regression analysis and resulted in: 1) The relationship between perceptions of quality candidates (candidates) and political beliefs (political trust) with political participation, the value of F = 1.056 with a significance level of 0.351> 0.05. It can be concluded that this hypothesis is rejected or not proven, that means there is no significant relationship between perceptions of quality candidates (candidates) and political beliefs (Political Trust) with Political Participation. 2) partial test results perceptions of the quality of candidates (X1) with political participation, the value of t = 0.297 and 0.767 significance level> 0.05. This suggests that partial perception of the quality factor candidates (candidates) (X1), there was no significant relationship to political participation (Y). It can be concluded that this hypothesis is not proven or rejected. 3) The results of the partial test of political beliefs (political trust) (X2) with political participation, the value of t = -1.424 and a significance level of 0.157> 0.05. This suggests that partial political trust factor (X2) there is no significant relationship to political participation (Y). value of R Square (R2) of 0.14. R Square value of 0.14 indicates the percentage contribution of the effect of independent variables (perception of the quality of candidates and political beliefs) on the dependent variable (political participation) only by 1.4%, while the remaining 98.6% is influenced by other variables not variables included in the study. Keywords : Perception of the quality of candidates, Political trust, Political participation.